MONEY LAUNDERING KAITANNYA DENGAN PEMERIKSAAN TINDAK PIDANA ASAL - Latief, Abd Rahman (Katalogis, 2017)
Problems Formulation: (1) Can money laundering be on trial without first judging the predicate offences? (2) How to prov money laundering before itsperdicate offences have been legally binding? The purpose of the research were to (1) identify and analyze money laundering without first judging its predicate offences and (2) identify how to prove money laundering before the verdict on its predicate offences have been legally binding. It was a normative research. The result of the research showed two points. (1) Money Laundering was a continued criminal offence (predicate offence). It could be factually judged without fist hearingÂ its predicate offences as it was independent and its predicate offences were not prerequisite to litigation against it, and there was no legal norm, either in criminal law of procedures or other laws ruling that predicate offences as a prerequisite to litigation Against money laundering. (2) The proving of money laundering before a verdict on a predicate offence had been legally binding, could adopt system commonly yused, i.e.: negative evidence and shifting burden of proof. However, without a verdict on the predicate offices, a money laundering could not be proved and the judgeâ€™s sentence tended to be not guilty.